Transformation of Gender Dominance in Russian TV Content in 2000s and 2010s: Based on Detective Series / Трансформация гендерной доминанты в российском телеконтенте 2000-х–2010-х гг. (на примере детективных сериалов) - Ilchenko Sergei N. / Ильченко С.Н. (Наука телевидения)
The article covers the gender issues of modern Russian television content on the example of a serial segment of Russian broadcast over the past 20 years. This aspect predetermines the relevance of the proposed research. The work focuses on the series that tend toward the most mass and popular forms of solving aesthetic problems—melodrama, comedy, and detective. The examples of the series, involved in the analysis, suggest that the gender dominance, characteristic of the previous stage of TV broadcasting development in Russia, has transformed significantly. This trend is indicated by the increasing importance of female characters in Russian detective series of the 2000s and 2010s. Notably, the process is instantiated by both quantitative and qualitative markers, including in terms of appeal to different historical periods which are reflected in the plots. At the same time, producers, including production teams of broadcasters, make active use of foreign experience, creating domestic versions of popular detective series filmed in other countries. Such circumstances of on-air content production can be explained by a combination of both objective (social, psychological) factors and subjective reasons (potential audience composition). Such aspects, taken together, generate complexes of plot and personified viewers’ expectations from watching the series. This situation forces the filmmakers and originators of new TV series to budge from traditional formats and creative techniques and take the factor of gender dominance into consideration. The latter, according to the author of the article, contributes to the transformation of the structure and content of the narrative of serial screen products that were standard for the previous stage of Russian TV broadcasting development. It can be stated that in modern television, the shares and roles of male and female characters in the plot constructions are “equalizing”. This, in turn, predetermines the thematic and genre variability of series, reflecting the orientation of Russian serial filmmakers on expanding the potential TV audience. В статье рассматривается гендерная проблематика современного российского телеконтента на примере сериального сегмента отечественного телевещания последних 20 лет. Данное обстоятельство и предопределяет актуальность предлагаемой научной работы. В фокусе исследования находятся сериалы, тяготеющие к наиболее массовым и популярным формам решения эстетических задач — мелодрама, комедия, детектив. На примере привлеченных к анализу российских сериалов формулируется вывод о существенной трансформации прежней гендерной доминанты, характерной для предыдущего этапа развития отечественного телевещания. Подобная тенденция обозначается усилением значения женских персонажей в отечественных детективных сериалах 2000-х–2010-х гг. Причем процесс характеризуется как количественными, так и качественными маркерами, в том числе и с точки зрения обращения к различным историческим периодам, которые находят отражение в сериальных сюжетах. При этом производители, включая продюсерские группы каналов-вещателей, активно используют зарубежный опыт, создавая отечественные версии успешных и популярных детективных сериалов, снятых в различных странах. Подобные обстоятельства производства эфирного контента объяснимы сочетанием как объективных (социальных, психологических) факторов, так и субъективными причинами (составом потенциальной зрительской аудитории), а это в совокупности и порождает комплексы сюжетных и персонифицированных ожиданий зрителей от просмотра сериалов. Такая ситуация вынуждает создателей и инициаторов новых сериалов отходить от привычных форматов и креативных приемов, используя фактор гендерной доминанты. Последняя, по мнению автора статьи, способствует трансформации привычных для предыдущего этапа развития отечественного телевещания структуры и наполнения нарратива создаваемого экранного продукта в формате сериала. Можно констатировать, что для современного телевидения характерно «выравнивание» доли и роли мужских и женских персонажей в сюжетных конструкциях выпускаемых в эфир сериалов. А это, в свою очередь, предопределяет их тематическую и жанровую вариативность, отражая нацеленность создателей отечественной сериальной продукции на расширение потенциальной зрительской телеаудитории.